Forcing Independent Domination Number of a Graph (European Journal of Pure and Applied Mathematics, 2019)
In this paper, we obtain the forcing independent domination number of some special graphs. Further, we determine the forcing independent domination number of graphsÂ  under some binary operations such join, corona and lexicographic product of two graphs.